Development and characterization of Al2O3-ZrO2 Composites Using ZrO2(Y2O3)-recycled as raw material - Cossu, Caio Marcello Felbinger Azevedo (2018)
The objective of this work was the development of Al2O3-ZrO2 ceramic composites using recycled-source of ZrO2(Y2O3). Al2O3 powder was mixed with different proportions of ZrO2(Y2O3) arising from pre-sintered blocks used in dental prostheses manufacturing. The mixtures containing 3wt% to 15wt% ZrO2(Y2O3) were uniaxially pressed at 80MPa and sintered at 1600°C-2h. Raw materials and sintered samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), relative density, hardness and fracture toughness. The results of X-ray diffraction showed α-Al2O3 and tetragonal-ZrO2 as crystalline phases after sintering. Furthermore, the relative density in all compositions was higher than 95%. The samples presented Vickers hardness and fracture toughness higher than 1300HV and 3.5MPa. m1/2, respectively.